Interstitial nephrocalcinosis and chronic glomerulonephritis in a bitch - Cahua U., Jacqueline (2018)
Diffuse nephrocalcinosis is a rare condition in dogs. It is reported the case of a one-year-old crossbred female dog with severe chronic renal failure, and bilateral diffuse renal mineralization detected by ultrasound. The histopathological diagnosis was a severe diffuse non-suppurative chronic glomerulonephritis with metastatic calcification and tubular atrophy.